Evaluation of stricture posterior urethra pre and post operatively with the help of retrograde urethrography with special reference to patient satisfaction - Singh, Rajkishore; Lonare, Rajesh; Mathur, R. K.; Ghanghoria, Arvind; Singh, Kulwant (International Surgery Journal, 2016)
Background:Urethral Stricture is defined as decrease in the caliber of the urethra, due to scar resulting from tissue injury or destruction. The stricture of the posterior urethra involves membranous and prostatic urethra. Changes in urologic imaging are occurring at a rapid rate. Methods:In this study, we evaluate the patient with posterior urethral stricture pre and post operatively with the help of retrograde urethrography with their satisfaction. We present our experience with 72 cases of posterior urethral stricture & its management with the help of retrograde urethrography, for the last 10 years. Results:All cases were male. Maximum age incidence is between 21-30 years age group i.e. 29 (40.27%). 45 cases (62.5%) were due to fracture pelvic and 20 (27.78%) cases were due to previous catheterization. Average age was 33.79 years. Length of stricture was mostly 1-3 cm. Average duration of follow up was 20.92 months. Outcomes in our series were good result in 49 (68.05%), fair result in 20 (27.78%) & poor result in 3 (4.16%) of the patients. Conclusions: In this study, retrograde urethrography defines the extent and the location of the stricture pre operatively and then extent of correction after the operation in various patient.